Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1017/jfm.2023.286
|View full text |Cite
|
Sign up to set email alerts
|

Non-modal perturbation growth in a laminar jet: an experimental study

Abstract: It is known that, apart from the growth of instability modes, the non-modal (algebraic) mechanism of linear growth plays an important role in near-wall flows. In unbounded flows, including submerged jets, the theoretical analysis of the non-modal growth mechanism started only in the last decade; this mechanism has not yet been identified in experiments. In the present work, experiments were conducted on the excitation of a non-modal ‘lift-up’ growth mechanism. Special wavy structures (deflectors) were introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…PIV measurements in the transverse cut plane of the jet, which are described in Ivanov et al [20] in detail and are not included in this short paper, showed that the evolution of introduced perturbation matches qualitative features of theoretical optimal perturbations quite well. Namely, the following characteristic features of the "lift-up" growth mechanism have been confirmed.…”
Section: Cross Section Visualization and Analysismentioning
confidence: 74%
See 4 more Smart Citations
“…PIV measurements in the transverse cut plane of the jet, which are described in Ivanov et al [20] in detail and are not included in this short paper, showed that the evolution of introduced perturbation matches qualitative features of theoretical optimal perturbations quite well. Namely, the following characteristic features of the "lift-up" growth mechanism have been confirmed.…”
Section: Cross Section Visualization and Analysismentioning
confidence: 74%
“…The lengthening of the petals occurs linearly, therefore, the radial velocity perturbation is approximately constant, which is consistent with the theoretical calculations of stationary optimal perturbations of the jet (see fig. 6a at Ivanov et al [20]).…”
Section: Cross Section Visualization and Analysismentioning
confidence: 96%
See 3 more Smart Citations